Pharmacotherapeutic follow-up in patients with arthrosis in a private pharmaceutical office - Flores Julián, Corina (2022)
The objective of this study was to carry out pharmacotherapeutic follow-up (SFT) in patients with osteoarthritis, evaluating the level of knowledge, pharmacotherapeutic adherence, identification of drug-related problem (DRP) and quality of life. It is a descriptive, observational and longitudinal study in twenty patients diagnosed with osteoarthritis. The data collection, from the patients recruited in a private pharmaceutical office, was carried out by means of instruments that consist of the formulation of surveys carried out in the patient’s home. The predominant sex was female (90%) and an age range of 56 to 60 years (40%), with comorbidities being arterial hypertension (45%), osteoporosis and diabetes mellitus, the average of the intensity measurement scale pain was reduced by 2 points (p<0.05) and quality of life improved (p<0.05). The level of knowledge about osteoarthritis was rated before and after the study, who managed to increase after the study to 18 patients (95% good rating). 90% of patients were non-adherent to treatment; the SFT was able to identify 57 PRM, the PRM 1 of necessity prevailed, which in 18 patients do not receive the medication they need, followed by the PRM 5, where 15 people suffer a health problem as a result of a non-quantitative insecurity of a drug and PRM 2. It is concluded that pharmacotherapeutic follow-up through pharmaceutical intervention has a positive impact on patients with osteoarthritis.